EARNINGS MANAGEMENT IN THE CONSTRUCTION SECTOR: AN EMPIRICAL ANALYSIS OF INVESTMENT, DISTRESS, AND ASYMMETRY IN INDONESIA - Diki Zachariah; Haninun (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the influence of investment opportunity set, financial distress, and information asymmetry on earning management in building construction companies listed on the Indonesia Stock Exchange for the 2021-2023 period. This study uses a quantitative approach that applies multiple linear regression analysis methods to identify the influence of each independent variable on the dependent variable. Sample selection was carried out by purposive sampling method which produced 30 samples from a total of 10 companies over a period of 3 years. The results of the study show that investment opportunity set has a significant negative effect on earning management while financial distress and information asymmetry have a significant positive effect on earning management. The more investment opportunities a company has, the more likely it is to reduce the tendency of earning management, while financial distress and information asymmetry actually increase the likelihood of earning management.